Accuracy of Manual and Virtual Predictive Tracings in Patients Submitted to Orthognathic Surgery - Gorla, Luís Fernando De Oliveira [UNESP]; Dos Santos, José Cleveilton; Carvalho, Pedro Henrique De Azambuja; Hochuli-Vieira, Eduardo; Gabrielli, Marisa Aparecida Cabrini (My University, 2023)
Cephalometric tracing done manually was considered gold standard for the cephalometric analysis in the last decades. The digital radiographs began to be commonly used in order to make that in a digital way. The objective was to define the accuracy of the predictive and final cephalometric tracings performed manually and virtually. The authors selected 20 patients submitted to bimaxillary orthognathic surgery. The data were collected from lateral cephalometric radiographs, in the preoperative and postoperative periods. The interest were: points, angles (Sella-Nasion to A point angle; Sella-Nasion to B point angle; Frankfurt plane to Mandibular plane angle; Frankfurt plane to occlusal plane angle; Upper and lower central incisors long axes angle; Incisor to Mandibular plane angle; Upper incisor axis to Sella-Nasion plane angle) distances (Co-A; Co-Gn). Data were submitted to the Shapiro-Wilk, analysis of variance, and Kruskal-Wallis tests. The measurement differences were compared using a t test. Descriptive statistics were performed in Excel 2013 and SPSS software, P<0.05 being considered significant. No statistically significant difference was found between the mean values predictive and postoperative of the angles and distances within the manual and digital groups. When comparing the means of the differences between the predictive values and the final values, only the 1:1 angle presented a statistically significant difference, indicating a greater accuracy of the digital predictive tracing for this measure. In conclusion, both methods for obtaining predictive tracings are accurate, which shows that clinical results can be successfully simulated by the most accessible technique.
Keywords: Cephalometry; computer diagnostics; orthognathic surgery